2012
DOI: 10.1177/0261018311435025
|View full text |Cite
|
Sign up to set email alerts
|

Children’s best interests and intimate partner violence in the Canadian family law and child protection systems

Abstract: This article summarizes the findings of a project investigating women's experiences with the Canadian child protection (CPS) and family law (FLS) systems. We examine both service systems together here because although both privilege children's best interests as their primary consideration and define the concept similarly, the two systems diverge in their expectations of women relative to child custody. While FLS requires women to accept custody arrangements that provide close and continued contact between them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These ongoing challenges in collaboration have real--world implication for families. In one qualitative Canadian study, women who had contact with both child welfare and DV service systems expressed frustration with the sometimes contradictory mandates of these respective paradigms of intervention, pointing to the need for continued attention to effective cross--system communication and collaboration (Hughes & Chau, 2012) Despite the historical separation and contrasts of child welfare and domestic violence interventions and policies, the delineations are diminishing as child protection systems increasingly regard domestic violence as a target of attention related to child safety and well--being. In other words, there is an expanding intersection of domestic violence and child maltreatment, and this intersection is being addressed by the child welfare system in their interventions with families.…”
mentioning
confidence: 99%
“…These ongoing challenges in collaboration have real--world implication for families. In one qualitative Canadian study, women who had contact with both child welfare and DV service systems expressed frustration with the sometimes contradictory mandates of these respective paradigms of intervention, pointing to the need for continued attention to effective cross--system communication and collaboration (Hughes & Chau, 2012) Despite the historical separation and contrasts of child welfare and domestic violence interventions and policies, the delineations are diminishing as child protection systems increasingly regard domestic violence as a target of attention related to child safety and well--being. In other words, there is an expanding intersection of domestic violence and child maltreatment, and this intersection is being addressed by the child welfare system in their interventions with families.…”
mentioning
confidence: 99%
“…At the same time, the lack of compliance of the return decisions with the standards laid out in the crc is not surprising, as the best interests of the child are not foregrounded in migration law (Goeman et al, 2014;Klaassen and Rodrigues, 2017;Langrognet, 2018). This situation contrasts with other areas of law such as juvenile criminal law (Lacombe, 2018), family law, and child protection law (Hughes and Chau, 2012), in which the best interests of children are assessed and determined in the process of making decisions that affect their lives.…”
Section: 1mentioning
confidence: 99%
“…Hartley (2004) found that workers pointed out a higher concern for safety when domestic violence is present in addition to child maltreatment and tended to opt for child removal in a higher percentage of cases. Hughes and Chau (2012) highlighted also the relevance for the CPS that the mothers leave their abusive partner to reduce the risk of removal of their children. However, this CPS's expectations may be in conflict-or at least partially divergent-to that of other systems, as the Family Law ones, that requires women to accept custody arrangements that provide close and continued contact between themselves and their former abusive partners (Hughes & Chau, 2012).…”
Section: Introductionmentioning
confidence: 99%